2011
DOI: 10.1111/j.1468-3083.2011.04043.x
|View full text |Cite
|
Sign up to set email alerts
|

Moderate correlation between quality of life and disease activity in adult patients with atopic dermatitis

Abstract: Disease activity correlated better with QoL when disease activity was less severe and disease extent ('rule of nines') correlated better with QoL than disease severity. An individual's improvement of 10 points in disease activity was accompanied by only a small improvement in QoL. Other factors than disease activity may influence QoL in patients with AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 40 publications
2
39
1
1
Order By: Relevance
“…This study clearly demonstrated the relationship between disease severity and patient quality of life, with the SCORAD index, PO-SCORAD and DLQI scores all having decreased significantly by 55-60% (p < 0.0001) from inclusion. The fact that the SCORAD index was fairly well correlated with the DLQI (r = 0.52, change from baseline) contrasts with the results of two recent studies [14,15], which both showed a poor correlation between the SCORAD index and DLQI.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…This study clearly demonstrated the relationship between disease severity and patient quality of life, with the SCORAD index, PO-SCORAD and DLQI scores all having decreased significantly by 55-60% (p < 0.0001) from inclusion. The fact that the SCORAD index was fairly well correlated with the DLQI (r = 0.52, change from baseline) contrasts with the results of two recent studies [14,15], which both showed a poor correlation between the SCORAD index and DLQI.…”
Section: Discussioncontrasting
confidence: 54%
“…This poor correlation can be logically explained by the fact that Van Valburg et al [14] and Haeck et al [15] used the objective SCORAD index, which does not take into account pruritus and sleep loss. Indeed, these 2 subjective symptoms, which are included in the SCORAD index and PO-SCORAD, play a major role in a patient's quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Reasons for this are unknown. Studies investigating this disconnect may help clinicians and researchers better understand the disease from the patient perspective and develop better outcome measures.…”
Section: Quality Of Lifementioning
confidence: 96%
“…A moderate correlation between HRQoL and disease activity is not a unique finding for CSU patients, but has also been noticed in different (dermatologic and other) conditions. For example, the DLQI score was found to have a relatively poor correlation with disease activity in an Italian population of psoriasis patients as well as in a Dutch population of atopic dermatitis patients [27,28]. Additionally, moderate correlations between disease activity and HRQoL were found in subjects suffering from inflammatory bowel disease [29].…”
Section: Discussionmentioning
confidence: 99%